2013
DOI: 10.2494/photopolymer.26.649
|View full text |Cite
|
Sign up to set email alerts
|

EUV Resist Materials Design for 15 nm Half Pitch and Below

Abstract: Chemically amplified resist materials with a different sensitivity were prepared to investigate impact of sensitivity on resolution at 15 nm half-pitch (hp) using a EUV microfield exposure tool (MET) at SEMATECH Berkeley. Sensitivity at least slower than 30 mJ/cm 2 was required to resolve 15 nm hp patterns using current EUV resists. It is noteworthy that resolution of 15 nm hp was limited by not only pattern collapse but also pinching of patterns. The same tendency is observed in E-beam patterning at 20 nm hp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…We have previously reported that combination of a high Tg and low Ea polymer with a large acid provides an apparently better L/S resolution with maintaining sensitivity [10,24]. In this study, we explored the same idea to determine how acid diffusion length contributes to block mask and isolated dot resolution.…”
Section: Influence Of Acid Diffusion Lengthmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that combination of a high Tg and low Ea polymer with a large acid provides an apparently better L/S resolution with maintaining sensitivity [10,24]. In this study, we explored the same idea to determine how acid diffusion length contributes to block mask and isolated dot resolution.…”
Section: Influence Of Acid Diffusion Lengthmentioning
confidence: 99%
“…Our previous study revealed that sensitivity more than 30 mJ/cm 2 is necessary to obtain realistic pattern quality on 15 nm hp and below if we utilize conventional CAR resist and process [10]. Recently Kocsis et al, reported that some metal containing resists can print 9.5 nm L/S using EUV interference lithography tool, but this resist also needs ~50 mJ/cm 2 sensitivity [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost exclusively, isotropic photoresists 1,[5][6][7] are employed and an enormous range of structures, components and devices is produced.…”
Section: Introductionmentioning
confidence: 99%